Clinical Pearls in Treatment of Zygomaticomaxillary Complex Fractures - Momeni Roochi, Mehrnoush; Hasheinasab, Mahboube; Afsar, Neda (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Zygomaticomaxillary complex (ZMC) fractures are common facial injuries that can significantly change the structure, function and esthetics of the midface. Proper and timely management of these fractures can reduce the rate of late complications. In this paper, we review the current literature regarding ZMC fracture treatment and discuss our experience from surgical treatment of multiple ZMC fractures in the course of 10 years.